Effect of Solvent on Kinetics of Reduction of Methyl Violet with Potassium Iodide at Different Temperatures - Saeed, R.; Ashfaq, M.; Razi Khan, S. (Asian Journal of Chemistry, 2010)
UV-visible absorption spectroscopy was used to study the effect of solvent on the kinetics of reduction of methyl violet with potassium iodide at various temperatures in water and mixed water alcohol system. The solvatochromism of methyl violet was studied at pH 4 and 6 by varying polarity of medium. Bathochromic shift was observed with decrease in polarity of solvent. The spectra showed that on decreasing polarity of medium i.e., from water to butanol the intensity of band increases. The ET values of the methyl violet in aqueous alcohol solvent showed that the position of the solvatochromic absorption band is dependent on the medium polarity. As the polarity increases λmax shifts to shorter wavelength causing hypsochromic shift. The rate of reaction of methyl violet with iodide at various pH slows down by the decrease of polarity as the formation of activated state takes longer time i.e. energy of activation increases. The other thermodynamic factors such as ΔS#, ΔG# and ΔH# were also evaluated and their changes as a function of variation of the polarity of the medium were observed.